TATA KELOLA TAMAN NASIONAL MERU BETIRI (TNMB) BERDASARKAN ASPEK GEOLOGI LINGKUNGAN - Januar Aziz Zaenurrohman; Januar Fery Irawan; Indra Permanajati; Sachrul Iswahyudi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Meru Betiri National Park (TNMB) is a natural conservation area related to land use that impact on the environment. Land-use suitability with land capability is essential so that the impact of the geological environment that can occur can be reduced and controlled. The research aims to determine the aspects of environmental geology and zoning land capability for governance of TNMB. Geological aspects of the environmental order that support this research are morphology (slope), lithology, hydrogeology (river density), and land cover. Each aspect is a parameter in the Analytical Hierarchy Process (AHP) evaluation method. The weight of each parameter of the AHP evaluation result is 26% for slope, 19% for lithology, 11% for river density, and 44% for land cover. The result of overlay parameters yields a score of each zoning and is classified into 4 (four) zoning land capabilities for governance of TNMB. The land use zone for governance of TNMB is divided into high capability zones, medium capability, low capability, and very low capability. High and medium capability zones can be used as conservation of TNMB primary forests.